How to leverage the initiative of regional innovation subjects under the digital economy? A study on the mediating effect of innovation environment - Lou, Yuan-yu; Yang, Guo-liang; Guan, Zhong-cheng (Technology analysis & strategic management, 2025)
The digital economy, as the most dynamic, innovative, and widely radiating economic form at present, has become an important force driving global economic development. Against this backdrop, how to leverage the initiative of innovation subjects and enhance regional innovation vitality has become an important issue. In view of this, this study explores the impact mechanism of the digital economy on the initiative of regional innovation subjects based on data from 30 regions in China, and analyzes whether the digital economy first affects the innovation environment and then influences the initiative of innovation subjects. The results show that the digital economy significantly enhances the initiative of regional innovation subjects, and as the scale of the digital economy continues to expand, it exhibits a non-linear feature of 'increasing marginal effects' on leveraging the initiative of regional innovation subjects. In addition, the regional innovation environment positively moderates the relationship between the digital economy and the initiative of innovation subjects. And it partially mediates the relationship between the level of the digital economy and the initiative of enterprises; While, it fully mediates the relationship between the level of the digital economy and the initiative of universities and research and development institutions.